2008
DOI: 10.1007/s10517-008-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of coenzyme Q10

Abstract: The pharmacokinetics of coenzyme Q10 powder and solution of solubilized form was studied after their oral administration to rats (10 mg/kg). Plasma concentrations of coenzyme Q10 were measured by HPLC with electrochemical detection over 48 hours. Solubilized coenzyme Q10 exhibited high absorption creating higher plasma concentrations of the drug, as a result of which its bioavailability constituted 264% of that for the powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Nevertheless these therapies could not primariy prevent lethal reperfusion injury, because of the slow enteric absorption of L-carnitine [138] and Coenzyme Q10 [139]. Some studies have suggested that antioxidant agents attenuate left ventricular remodeling following AMI.…”
Section: Clinical Experiences Of Antioxidant Treatment Of Myocardimentioning
confidence: 99%
“…Nevertheless these therapies could not primariy prevent lethal reperfusion injury, because of the slow enteric absorption of L-carnitine [138] and Coenzyme Q10 [139]. Some studies have suggested that antioxidant agents attenuate left ventricular remodeling following AMI.…”
Section: Clinical Experiences Of Antioxidant Treatment Of Myocardimentioning
confidence: 99%
“…This has led many investigators to exclusively report TQ10 [23], by either chemically reducing samples with NaBH 4 [24] or oxidizing them with FeCl 3 or CuCl 2 [20] before analysis or by precolumn electrochemical reduction or oxidation [5]. The most popular routine analysis employs reversed-phase HPLC with absorbance readings at 275 nm [25] or electrochemical detection to achieve higher sensitivity.…”
mentioning
confidence: 99%
“…Due to its insolubility in water, limited solubility in lipids, and its relatively high molecular weight, CoQ10 has a poor and slow-rate absorption with a T max value of about 6 hr (Bhagavan & Chopra, 2006). At 24 hr following oral administration, a second plasmatic peak is observed, which could be attributed to enterohepatic recirculation and a redistribution from liver to circulation by lipoproteins (Kalenikova, Gorodetskaya, & Medvedev, 2008). VLDL, LDL, and HDL carry a 16%, 58%, and 26% of serum CoQ10, respectively, and it is believed that CoQ10 is capable to prevent them from oxidation (Tomasetti, Alleva, Solenghi, & Littarru, 1999).…”
Section: Pharmacokinetics and Bioavailability Of The Dietary Supplemementioning
confidence: 99%